Visual Servoing With Application To ROV For Ship Hull Inspection. - Zainal Abidin, Zulkifli; Arshad, Mohd Rizal (2006)

(untitled)
A novel method for surface tracking for ship hull inspection is presented. The proposed method is based on the USM-ROV visual surface tracking.